Interface: The search for legibility of urban form for African migrants in Cape Town, South Africa - Mutia, Kevin Ngumbao (School of Architecture, Planning and Geomatics, 2024)
In moving, fleeing or travelling to a different country for a myriad of reasons, migrants find themselves in new contexts, new worlds sometimes completely different from the places they come from. This makes them a vulnerable proportion of society in the urban spaces they find themselves in. Further this added complexity in understanding a new context comes as a concern in terms of navigating new urban spaces, seeking shelter, and creating livelihoods in these 'new worlds'. A plethora of borders and barriers to integration and adaptation exist in the host urban setting. From language barriers, to financial and cultural exclusion, host community xenophobic attitudes, further to being a foreigner in a foreign land with different urban structures and ways of life. In the quest to seek shelter and find settlement and creating livelihoods, migrants find themselves navigating new urban structures and forms which are unlike where they come from. From creating Lynch's mind maps to assist in mental mapping of one's physical spaces, migrants identify paths, nodes, edges, districts and landmarks from their own perspectives that create a layer of urban space that in most cases lacks to be incorporated in urban planning and design consideration for our cities that are 'worlding' (Ong, 2011; 10) by becoming more diverse by the day. The two outermost tips on the continent of Africa present two different cites with similar themes of exclusion of migrants in accessing the proverbial 'better life'. From Mellila's exclusionary borders, high-fence, razed wire barriers to Cape Town's exclusionary urban structure, migrant narratives from the north to the south of Africa are riddled with stories of exclusion, fear and being 'othered'. In seeking to address notions of acceptance, integration and adaptation. The project aims to provide a leeway in addressing the plights of the African migrant in urban space in cities on the continent by focusing on a case example in Cape Town to assess how strategic interface locations in the city can allow for 'worlding' by celebrating diversity and enabling rights to the city for all including the 'other'. Hence this research project seeks to gain an understanding into the lived experience of African migrants in the production of urban space through everyday migrant urbanism in Cape Town.